Ceramic industry at Morbi as a large source of SO2 emissions in India. (15th February 2020) - Kharol, S.K.; Fioletov, V.; McLinden, C.A.; Shephard, M.W.; Sioris, C.E.; Li, C.; Krotkov, N.A.
Abstract: Observations from the Ozone Monitoring Instrument (OMI), onboard the NASA's Earth Observing System (EOS) Aura satellite, reveal a large SO2 "hotspot" over Morbi, Gujarat, India, while the available emissions inventories do not report any major sources in this region. There are no industries that are typically associated with the elevated SO2 such as large power plants, smelters, or oil refineries in the Morbi region. Our analysis shows that the elevated SO2 source is attributed to the ceramic industries in an area of ~7 × 7 km 2 near the city. OMI-estimated SO2 emissions from the Morbi ceramic industries have been near or above 100 kt y −1 since 2009, which are similar to emission levels from larger Indian oil refineries (such as Essar and Jamnagar) and power stations (such as Mundra Thermal Power Station and Ultra Mega Power Plant) located in Gujarat, India. According to OMI measurements, the SO2 emissions from the Morbi ceramic industries are presently five times higher than they were in 2005. This study demonstrates that in the absence of any other information about SO2 emissions from the ceramic industry, these satellite-based estimates can fill the gap in emission inventories in a timely fashion. Highlights: First satellite estimates of SO2 emissions from India's Morbi ceramic industry. SO2 ceramic emissions are similar to those from large refineries and power plants. Morbi ceramic SO2 emissions are ~5 times higher in 2017 compared to 2005.